Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1200/jco.2013.31.15_suppl.tps11123
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study utilizing molecular profiling to find potential targets and select individualized treatments for patients with metastatic breast cancer.

Abstract: TPS11123 Background: The objective of this prospective pilot study was to determine if treatment selected by molecular profiling (MP) of metastatic breast cancer (MBC) tumors at time of disease progression provides greater clinical benefit than empiric treatment selection. Methods: Eligible pts had MBC, ≥ 3 prior lines of therapy, and > 6 wks - < 6 months time to progression on last treatment prior to study entry. Fresh core biopsy samples were taken from the metastatic site for MP. Analysis by IHC, FIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated the feasibility and potential clinical benefit of the MP-guided approach in a variety of refractory cancers and in metastatic breast cancer where it resulted in a ≥30% longer progression-free survival than for the last (pre-MP) regimen on which the patients progressed in 27% and 52% of cases, respectively [ 17 , 18 ]. Although the progression-free survival ratio endpoint was inappropriate for our study, as most of the patients did not receive pre-MP chemotherapy for metastatic disease, our findings are compatible with these earlier studies and support the need for further investigations of MP-guided therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the feasibility and potential clinical benefit of the MP-guided approach in a variety of refractory cancers and in metastatic breast cancer where it resulted in a ≥30% longer progression-free survival than for the last (pre-MP) regimen on which the patients progressed in 27% and 52% of cases, respectively [ 17 , 18 ]. Although the progression-free survival ratio endpoint was inappropriate for our study, as most of the patients did not receive pre-MP chemotherapy for metastatic disease, our findings are compatible with these earlier studies and support the need for further investigations of MP-guided therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It involves the application of immunohistochemistry (IHC), fluorescent/chromogenic in situ hybridization (FISH/CISH), microarray analyses, sequencing, and reverse transcription polymerase chain reaction (RT-PCR). Treatment based on MP findings has proved successful in a pilot study of a variety of refractory cancers and a separate study of metastatic breast cancer [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in patients with refractory breast cancer showed that tumor profiling resulted in a revision of the original treatment decision for all patients. Tumor profiling based therapy resulted in a clinical benefit in 52% of heavily pretreated patients ( Jameson et al, 2013 ). A review of all patients treated in a single center in Australia resulted in clinical and survival benefits in over half of the patients and confirmed the role of molecular profiling in a clinical practice setting ( Dean and Wallace, 2013 ).…”
Section: Clinical Evidence Supporting Use Of CMImentioning
confidence: 99%
“…Indeed, this high‐throughput multiplex platform allows for broad investigation into the changes in the signaling architecture of the malignant cells starting from very small amounts of biological material such as a core needle biopsy. Moreover, by constructing each array with built in standard curves and controls, the RPPA platform is currently capable of delivering quantitative information that can be easily used for stratifying patients for individualized treatment .…”
Section: Introductionmentioning
confidence: 99%